Implikasi Yuridis Putusan Judicial Review UU No. 9 Tahun 2009 tentang Badan Hukum Pendidikan - Shanti Dwi Kartika (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2010)
The Constitutional Court verdict Number 11-12-21-126-136/PUU-VII/2009, dated March 31st, 2010, related to judicial review of Law Number 9 in 2009 on Educational Legal Entity, granted the request of the applicant for the most part. One of the ruling of the Constitutional Court stated that Law Number 9 of 2009 on Educational Legal Entity contrary to the State Constitution of the Indonesia Republic 1945 and has no binding legal force. The Constitutional Court verdict brings implications on education in Indonesia. This essay analyzes the juridical implications of The Constitutional Court verdict Number 11-12-21-126-136/PUU-VII/2009. Juridical implications of the verdict related to the existence of a legal vacuum (rechtvacuum) and the implementation levels of education. Juridical implications influence legislation governing the management and implementation of education, especially the education unit of goverrnance. Therefore, it is necessary immediately to establish a law as a substitute for The Law of Educational Legal Entitiy and do a redesign for the conductor of the educational unit.